Application of C4.5 Algorithm in Improving English Skills in Students - Septri Wanti Siahaan; Kristin Daya Rohani Sianipar; P.P.P.A.N.W Fikrul Ilmi R.H Zer; Dedy Hartama (Jurnal Informatika Universitas Pamulang, 2020)
In this world, many languages from other countries can be used as a communication tool. One of them is English. Students who has qualification must know that learning English is very much needed. Because nobody knows what will happen in the next few years. It could be one factor to obtain a position the next few years is our expertise in speaking English. English is a global language used by people to communicate with other people. On this occasion, researchers conducted research to determine what factors can improve students' ability to speak English. To complete this research, researchers resolve by applying the existing algorithm in data mining, namely C4.5 Algorithm. The result of this research can be concluded that the factors that influence to improve students ability in English are hearing from the environment.